Meningkatkan keterampilan sosial pasien skizofrenia katatonik melalui social skill training - Muhamad Febrian Al Amin (Universitas Muhammadiyah Malang, 2021)
Social interaction in people with schizophrenia is a serious problem, because if it is not treated it will make the situation worse. This case study aims to improve social skills in people with schizophrenia using Social Skills Training. Psychological assessment using interviews, observation, Wechsler Adult Intelligence Scale (WAIS), Graphic Test, and Sack’s Sentence Completion Test (SSCT). The subject is 18 year old male. The results of the intervention showchanges in the form of being able to say hello, introduce yourself ﬁrst, interact with people around, and the subject is no longer in the room often.